2007
DOI: 10.1111/j.1467-9280.2007.01842.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cooperation and Competition

Abstract: ABSTRACT-Evolutionary scientists argue that human cooperation is the product of a long history of competition among rival groups. There are various reasons to believe that this logic applies particularly to men. In three experiments, using a step-level public-goods task, we found that men contributed more to their group if their group was competing with other groups than if there was no intergroup competition. Female cooperation was relatively unaffected by intergroup competition. These findings suggest that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
161
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(185 citation statements)
references
References 23 publications
19
161
3
2
Order By: Relevance
“…The arguments put forth by Archer (2009) that sexual selection best explained human sex differences in aggression has found strong supporting evidence in tendencies toward competition and cooperation, among other areas. Van Vugt, De Cremer, and Janssen (2007) for example, found that men give more to their groups when such groups are in competition with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The arguments put forth by Archer (2009) that sexual selection best explained human sex differences in aggression has found strong supporting evidence in tendencies toward competition and cooperation, among other areas. Van Vugt, De Cremer, and Janssen (2007) for example, found that men give more to their groups when such groups are in competition with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 281: 20141539 differences in the decision behaviour of men and women in reaction to between-group competition have also been found [71][72][73].…”
Section: (D) Studies On the Psychology Of Human Intergroup Relationsmentioning
confidence: 91%
“…A third alternative perspective on individual motivations for engaging in intergroup aggression is the 'male warrior hypothesis' proposed by van Vugt & co-workers [71,72]. It builds on the observations that it is mostly men who engage in violent intergroup conflicts, that proven warriors seem to be perceived as more attractive and might have increased reproductive success, and that in laboratory experiments men frequently react differently to the presence of intergroup contest than women.…”
Section: (C) the Male Warrior Hypothesismentioning
confidence: 99%
“…No research, however, has yet examined how others perceive these dangerous, high fWHR males, specifically regarding when and why other individuals might choose to associate with them. Given the coalition-based nature of human evolution and conflict (McDonald, Navarrete, & Van Vugt, 2012;Van Vugt, De Cremer, & Janssen, 2007), understanding the conditional acceptance of these individuals is critical to understanding why fWHR might persist as an honest signal of physical strength or aggression.…”
Section: The Current Researchmentioning
confidence: 99%